A nondestructive method of identifying pigments on canvas using low frequency electron paramagnetic resonance spectroscopy. Issue 1 (3rd April 2018) - Javier, Stephany; Hornak, Joseph P.
ABSTRACT: Electron paramagnetic resonance (EPR) spectroscopy is a useful analytical tool for studying objects with cultural heritage significance. It is generally thought of as a destructive spectroscopy, owing to the small sample size, and thus not used to study paintings. We demonstrate that a form of this spectroscopy known as low frequency EPR spectroscopy can be used to nondestructively identify ultramarine blue, Egyptian blue, Han blue, rhodochrosite, blue vitriol, terracotta red, charcoal, and coal pigments in a linseed oil paint on canvas.